2021
DOI: 10.1108/sasbe-03-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Smarter real estate marketing using virtual reality to influence potential homebuyers' emotions and purchase intention

Abstract: PurposeThis paper aims to investigate the potentials of virtual reality (VR) for residential real estate marketing to influence house purchase intention.Design/methodology/approachBased on the relevant literature in consumer behaviour, this study hypothesised the relationships between atmosphere with pleasure and arousal emotions and the subsequent influence of emotions towards house purchase intention in a virtual environment. A within-subjects experimental design was conducted with 60 real potential homebuye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…Hence, the three bounded rational behaviours helped to explain the decision-making of homebuyers when they acquire/sell a property. This study has complemented the existing real estate marketing literature (such as Azmi et al , 2021; Hassan et al , 2021; Zhao and Chen, 2021) on housing purchase decisions. In theoretical implications, this research examined the homebuyers’ choice behaviour using behavioural economics models from the perspectives of emotion and heuristics judgment, where previous studies dominantly used neoclassical economics models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the three bounded rational behaviours helped to explain the decision-making of homebuyers when they acquire/sell a property. This study has complemented the existing real estate marketing literature (such as Azmi et al , 2021; Hassan et al , 2021; Zhao and Chen, 2021) on housing purchase decisions. In theoretical implications, this research examined the homebuyers’ choice behaviour using behavioural economics models from the perspectives of emotion and heuristics judgment, where previous studies dominantly used neoclassical economics models.…”
Section: Discussionmentioning
confidence: 99%
“…However, these research studies ignore the importance of decision-making of the individual homebuyers. Several recent studies focused on real estate marketing to influence homebuyers’ emotion and purchase intention in a virtual environment (Azmi et al , 2021), green housings (Zhao and Chen, 2021), as well as factors that influence housing purchase decisions (Hassan et al , 2021). However, very little to no attention is paid to cognitive psychology and heuristic biases.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal deceleration effect could attribute to consumers' lack of experience in the Determinants of VR adoption use of VR tour functions, hurting both the consumers' purchase experience and the property's selling process. Azmi et al (2021) investigated the adoption of VR as a smarter way of influencing the emotion and purchase intention of potential homebuyers. The study proposed a framework of four constructs: atmosphere, pleasure, arousal and house purchase intention.…”
Section: Empirical Studies On Vr Adoptionmentioning
confidence: 99%
“…Du et al (2018) showed that co-presence in VR can enhance stakeholder communication and design decisions made. The potential of VR has also been tested in the real estate sector to understand potential homebuyers' emotions and purchase intentions (Azmi et al, 2021). The results of this study indicate that VR can evoke pleasure and emotional arousal similar to that of a real-world environment.…”
Section: 2virtual Reality In the Aec Industrymentioning
confidence: 87%